Pengembangan Media Pembelajaran Pop-Up Book Materi Perkembangan Teknologi Transportasi Bahasa Indonesia Kelas III SD - Putri, Nur Oktafiani; Suryarini, Diah Yovita; Jarmani, Jarmani (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
The author is writing describe development of 3D Learning media in the form of pop-up book for Bahasa Indonesia lesson with lesson material development of transportation technology for third grader elementary school. The learning media development in this study obtained its feasibility throughh media expert and material expert. This writting is in the form of qualitative using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The author uses data collection techniques based on validity tests conducted by media masterful and material masterful. The results of writing a 3D learning media pop-up book for Indonesian subjects material development of third-grade elementary school technology that is included in the category of feasible/valid with the results of the media expert test reaches a percentage of 83.92% with validd criteria. While the results of the expert material test I reached a percentage of 77.08% with sufficient criteria valid/feasible and the results of the expert test material II reached a percentage of 100% with valid criteria / feasible. Based on the validity test, it can be summarized that the Pop-Up media that was developed entered into the criteria is valid/feasible so that this media is feasible and can be implemented in the classroom prac tice.Keywords: 3D Learning media, Pop-Up Book, Bahasa Indonesia, Development of Transportation Technology